Dynamical systems and congruence relations. Issue 1 (2nd January 2019) - Ostadhadi-Dehkordi, S.; Karimi Amaleh, M.
ABSTRACT: This study is an endeavour to construct the tensor products and the direct limits of dynamical systems through the utilization of the congruence relations and also to investigate the basic properties of the respective concepts. Moreover, the application of such relations entailed the reification of the quotient dynamical systems as well as isomorphism theorems.